2013
DOI: 10.3892/ijo.2013.2186
|View full text |Cite
|
Sign up to set email alerts
|

Adult, embryonic and fetal hemoglobin are expressed in human glioblastoma cells

Abstract: Hemoglobin is a hemoprotein, produced mainly in erythrocytes circulating in the blood. However, non-erythroid hemoglobins have been previously reported in other cell types including human and rodent neurons of embryonic and adult brain, but not astrocytes and oligodendrocytes. Human glioblastoma multiforme (GBM) is the most aggressive tumor among gliomas. However, despite extensive basic and clinical research studies on GBM cells, little is known about glial defence mechanisms that allow these cells to survive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…91,92 Thereafter, analyses confirmed the presence of different HBs (α, β, γ, δ, ζ, and ε) in human GBM cells under normal conditions, indicating reactivation of fetal and embryonic genes and their potential in inherent resistance of GBMs. 93 However, expression of these HBs did not differ between GBM cells with differing resistances to hypoxia and radiation. 93 Nonetheless, these results were obtained from monolayer cultures that do not mimic the pathophysiologic features of tumors with differential distribution of hypoxic areas and cell-to-cell contacts.…”
Section: Hb Expressions In Human Gbm Tumor Cell Linesmentioning
confidence: 88%
See 1 more Smart Citation
“…91,92 Thereafter, analyses confirmed the presence of different HBs (α, β, γ, δ, ζ, and ε) in human GBM cells under normal conditions, indicating reactivation of fetal and embryonic genes and their potential in inherent resistance of GBMs. 93 However, expression of these HBs did not differ between GBM cells with differing resistances to hypoxia and radiation. 93 Nonetheless, these results were obtained from monolayer cultures that do not mimic the pathophysiologic features of tumors with differential distribution of hypoxic areas and cell-to-cell contacts.…”
Section: Hb Expressions In Human Gbm Tumor Cell Linesmentioning
confidence: 88%
“…93 However, expression of these HBs did not differ between GBM cells with differing resistances to hypoxia and radiation. 93 Nonetheless, these results were obtained from monolayer cultures that do not mimic the pathophysiologic features of tumors with differential distribution of hypoxic areas and cell-to-cell contacts. Changes in HB expressions with experimental hypoxia in GBM cell lines were also analyzed.…”
Section: Hb Expressions In Human Gbm Tumor Cell Linesmentioning
confidence: 88%
“…Recently, the expression of Ngb and its homologous Cygb were also investigated in various cancers. Emara et al (2010Emara et al ( , 2014 reported that Ngb/Cygb was widely expressed in many cancers through microarray analysis. However, Gorr et al (2011) reported that Ngb, but not Cygb, was elevated in only a few types of tumors.…”
Section: Role Of Neuroglobin In Hccmentioning
confidence: 99%
“…The hypoxic upregulation of Hb expression in glioblastoma multiforme cells may be a part of a repertoire of active defense and adaptation mechanisms enabling these cells to acquire resistance to chemotherapy and radiotherapy. Therefore, new therapeutic strategies are required to interfere with Hb expression or function in glioblastoma multiforme cells .…”
Section: Hemoglobinmentioning
confidence: 99%
“…Mammalian nerve globins colocalize not only in the brain and in the neuronal retina but also in different tissues and organs . The concentration of mammalian nerve globins is generally ∼1 μM ; Ngb has been found at relatively high concentration in neurons of the hypothalamus reaching high levels (from 100 to 200 μM) in the retina rod cells .…”
Section: Introductionmentioning
confidence: 99%